Pengaruh Kedisiplin Guru Terhadap Motivasi Belajar Siswa Di Sekolah Essa Edutama Palembang - Muhammad Al Rafi Luki; Krsitiana Sri Utami (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to find out whether discipline and motivation influence student learning at the Essa Edutama School in Palembang. This type of research is included in quantitative research. This research was conducted at the ESSA EDUTAMA PALEMBANG school. The population in this study were teachers at the ESSA EDUTAMA PELMBANG school, totaling 20 teachers. The sampling technique used in this research is saturated sampling. In data collection carried out using primary data, primary data is by distributing questionnaires to respondents. The data collection technique in this research is a questionnaire. This research was analyzed using multiple linear regression using the IBM SPSS Statistics 25 program. Variable measurements used a Likert Scale: Strongly Agree (weight 4), Agree (weight 3), Disagree (weight 2), and Strongly Disagree (weight 1). The analytical tool used in this research is: T test. It is hoped that the results of this research will serve as a basic reference later in making a thesis proposal, so that this research method will study procedures regarding teacher discipline on student learning motivation. Research and includes activity steps, as well as research methods that will later be used. The conclusion in this research is that it can be concluded that the analysis of teacher discipline on student learning motivation influences each other. This can also be seen if teacher discipline increases, student learning motivation will also increase so that there can be a positive and significant influence between teacher discipline on student learning motivation. at the Essa Edutama Palembang school.